The Palm Beach murders : thrillers - Patterson, James, 1947- author.; Born, James O., author.; Arnold, Tim (Journalist), author.; Swierczynski, Duane, author. 262654 (New York, NY : Grand Central Publishing, 2021)
Includes bibliographical and references